2017
DOI: 10.3390/biomedicines5020032
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Analyses of Al2O3-Treated Titanium Plates Tested with Osteocyte and Fibroblast Cell Lines

Abstract: Osseointegration of a titanium implant is still an issue in dental/orthopedic implants durable over time. The good integration of these implants is mainly due to their surface and topography. We obtained an innovative titanium surface by shooting different-in-size particles of Al2O3 against the titanium scaffolds which seems to be ideal for bone integration. To corroborate that, we used two different cell lines: MLO-Y4 (murine osteocytes) and 293 (human fibroblasts) and tested the titanium scaffolds untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Alumina possesses high modulus of elasticity, compressive strength, and its bio inert behavior helps bone regeneration process and does not impair the cyto compatibility 17,18 . Aluminum oxide addition not only improves the mechanical properties but also good and sustained biocompatibility 17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Alumina possesses high modulus of elasticity, compressive strength, and its bio inert behavior helps bone regeneration process and does not impair the cyto compatibility 17,18 . Aluminum oxide addition not only improves the mechanical properties but also good and sustained biocompatibility 17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Cu exerts a very low cytotoxicity in human cells (TC50 value of 344±4.4 M in human gingival fibroblast [47]). Here, we tested the TiCu(Ag) thin films biocompatibility using MRC-5 human fibroblasts, a cell line widely used to perform cytotoxicity assays [48][49][50][51][52][53][54][55][56]. Human fibroblasts are responsible for synthesizing and depositing ECM components, mediate epithelial-mesenchymal interactions allowing other cells to settle and migrate along a three-dimensional support and thereby generating an organ-specific architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the composites prepared through the combination of bioactive and bioinert ceramics show better bioactivity and mechanical strength [39]. Typical examples are HA and Al 2 O 3 composites which show better osteointegration with bone, good bioactivity, and high yield strength [40,41].…”
Section: Ceramicsmentioning
confidence: 99%